Analysis of end-of-life treatment and physician perceptions at a university hospital in Germany - Schleicher, Nicole; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter; Büttner, Sylvia; Gencer, Deniz (Journal of cancer research and clinical oncology, 2022)
Purpose  Providing state-of-the-art palliative care is crucial in all areas of in- and outpatient settings. Studies on the implementation of palliative care standards for dying patients are rare. - Methods  N = 141 physicians from all internal departments were polled anonymously about the treatment of dying patients using a self-designed questionnaire. Furthermore, we evaluated the terminal care of n = 278 patients who died in internal medicine departments at University Hospital Mannheim between January and June, 2019 based on clinical data of the last 48 h of life. We defined mandatory criteria for good palliative practice both regarding treatment according to patients’ records and answers in physicians’ survey. - Results  Fifty-six physicians (40%) reported uncertainties in the treatment of dying patients (p < 0.05). Physicians caring for dying patients regularly stated to use sedatives more frequently and to administer less infusions (p < 0.05, respectively). In multivariate analysis, medical specialization was identified as an independent factor for good palliative practice (p < 0.05). Physicians working with cancer patients regularly were seven times more likely to use good palliative practice (p < 0.05) than physicians who did not. Cancer patients received good palliative practice more often than patients dying from nonmalignant diseases (p < 0.05). - Conclusion  Guideline-based palliative care for dying patients was found to be implemented more likely and consistent within the oncology department. These results point to a potential lack of training of fellows in non-oncological departments in terms of good end-of-life care.
Published online: 5 May 2021
Gesehen am 12.06.2023